Mealtime emotional climate and child health: A systematic review. (January 2022) - Smith, Jasmin A.; Saltzman, Jaclyn A.; Dev, Dipti A.
Abstract: Background: Positive mealtime emotional climate (MEC) has been linked to better nutrition, psychosocial, literacy and academic outcomes, and fewer behavior problems. However, MEC has been defined in a variety of ways across studies, limiting the ability to synthesize findings and plan future research. Objective: To identify which child characteristics are associated with MEC and to determine how previous studies have measured MEC. Methods: We searched three databases (1980–2020) for peer-reviewed articles measuring MEC. Inclusion criteria required at least one child-level outcome related to physical, nutritional, or developmental health; children aged 0–18 years old; and quantitative data using cohort, case-control, intervention, or experimental designs. We used a previously published taxonomy to categorize child/adolescent characteristics as correlates, non-correlates, unclear, or as having insufficient evidence, according to the amount of evidence linking them to MEC. Additionally, we extracted data about the measures and definitions of MEC from each included article. Results: Out of 668 unique studies identified in the initial search after duplicates removed, 14 met inclusion criteria, and only three used the same measure of MEC. Healthful dietary intake, disordered eating behaviors, and weight/BMI were categorized as correlates of MEC, but links to unhealthy dietary intake are unclear. Several characteristics (e.g. temperament, academic success) were examined in one study only. Conclusions: Future research should examine the relationship between MEC and child psychosocial child outcomes and utilize a preschool age group. These findings aid in conceptualizing how MEC has been defined and measured and illuminate the importance of MEC on children's health. Highlights: The field lacks a common measure for mealtime emotional climate. Dietary intake, body mass index/weight status, and disordered eating behaviors are correlates of mealtime emotional climate. More research is needed to examine child developmental correlates of mealtime emotional climate.